REFORMASI BIROKRASI DALAM MENINGKATKAN KINERJA APARATUR PADA DINAS KOPERASI, UMKM, PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN PESISIR SELATAN PROVINSI SUMATERA BARAT - Permana, Briyam Ksatria (Institut Pemerintahan Dalam Negeri, 2019)
Cooperatives, SMEs and trade sector of South Pesisir have not been maximized in supporting the people’s economy. Even the number of cooperatives and SMEs of South Pesisir Regency is still relatively minimal that of 333 the number of cooperatives, only 221 active cooperatives and only 69 cooperative srunning RAT. Also from 4440 the number of SMEs only 210 who have received coaching. In order to make the Cooperatives, SMEs and Trade as the main sector in supporting the economy of South Pesisir community, it is necessary to improve the performance apparatur of the Cooperative, SME, Trade and The Industry of South Pesisir Regency in conducting the cooperative and SMEs in the South Pesisir Regency. So that needed Bureaucratic Reform in improving performance of apparatus of Cooperatives, SME, Trade and Industry office of South Pesisir Regency. This research aims to determine and describe the form of Bureaucratic Reform that is applied and its effect on the performance of apparatus in Cooperatives, SME, Trade and Industry Office of South Pesisir Regency of West Sumatra Province. This research uses Descriptive Method with Inductive approach and data collection technique using Triangulation technique consist of interview technique, observation, and documentation. This research concludes that Bureaucratic Reform has been applied well in Cooperatives, SME, Trade and Industry Office of South Pesisir Regency, so that have improved apparatus performance. However, the implementation of Bureaucratic Reforms leads to quite fundamental changes that require adjustment. Therefore, socialization related to the changes that occurred, the provision of new SOP hardcopy and supervision attached to the apparatus.